2014
DOI: 10.1016/j.inoche.2014.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and photocatalytic behavior of cobalt(III) 5,10,15,20-tetrakis(1-methylpyridinium-4-yl)porphyrin

Abstract: Although kinetically inert cationic Co(III)TMPyP 5+ (H2TMPyP 4+ = 5,10,15,20-tetrakis(methylpyridinium-4-yl)porphyrin) was considered earlier to be very weakly emissive, both the spectrum and the lifetime of its fluorescence could be determined. Besides, this complex proved to be favorable for outer-sphere photoinduced reduction of the metal center in the presence of triethanolamine (TEOA) as electron donor quenching the triplet excited state of this metalloporphyrin. The corresponding cobalt(II) porphyrin for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
(35 reference statements)
3
18
0
Order By: Relevance
“…Nevertheless, the fluorescence lifetimes for these two spin states slightly deviated: 1.36 ns for the square planar and 1.19 ns for the octahedral complex. The fluorescence quantum yield at Soret-band excitation (fl = 2.010 -3 ) is in the same order of magnitude as that observed earlier for Co(III)TMPyP 5+ (9.910 -4 [7]). The higher value may be attributed to the larger ionic radius of Ni(II) (63 vs. 55 pm [18]) causing a smaller distortion (shrinkage) of the porphyrin ring.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…Nevertheless, the fluorescence lifetimes for these two spin states slightly deviated: 1.36 ns for the square planar and 1.19 ns for the octahedral complex. The fluorescence quantum yield at Soret-band excitation (fl = 2.010 -3 ) is in the same order of magnitude as that observed earlier for Co(III)TMPyP 5+ (9.910 -4 [7]). The higher value may be attributed to the larger ionic radius of Ni(II) (63 vs. 55 pm [18]) causing a smaller distortion (shrinkage) of the porphyrin ring.…”
supporting
confidence: 85%
“…Due to this band slightly redshifted compared to that of the free base, Ni(II) porphyrins were categorized as hypso type [4,27]. The emission spectrum displayed by Ni(II)TMPyP 4+ upon Soret-band excitation (Fig 2) is very similar to those of the corresponding cationic Co(III) and Mn(III) metalloporphyrins [7,17]. The fluorescence bands in the 550-800-nm range of the fluorescence spectra of porphyrins, both metalloporphyrins and free bases, can be assigned as S1S0 transitions (the individual bands correspond to the (0, 0), (0,1) and (0,2) transitions with respect to vibrational states -the latter one is generally not perceptible ) [19].…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…According to the generally accepted concept, earlier the highly distorted complexes with Mn(III) or Co(III) metal center were considered not to display appreciable fluorescence at room temperature [4]. However, in recent studies characteristic emission spectra were observed in the case of Co(III)TMPyP 5+ [5] and manganese(III) complexes with 5-[4-(5-carboxy-1-butoxy)-phenyl-10,15,20-tris(1-methylpyridinium-4-yl)porphyrin [6], 5,10,15,20-tetraphenylporphyrin, and 5,10,15,20-tetra(3-hydroxyphenyl)porphyrin [7].…”
Section: Introductionmentioning
confidence: 99%